Pelatihan Pembuatan Kompos pada Facility Care untuk Mengurangi Jumlah Sampah Organik di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi - Putri, Fitria Eka; Hubaybah, Hubaybah; Lesmana, Oka; Putra, Ashar Nuzulul; Fitri, Adelina (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
The Faculty of Medicine and Health Sciences, Jambi University (FKIK-UNJA) is one of the educational institutions contributing to organic waste in Jambi City, both from food scraps, as well as leaf waste and other organic waste. Based on preliminary studies and the results of interviews with 3 FKIK Facility Care officers and one FKIK UNJA Facility Care supervisor, information obtained by facility care officers has not separated waste based on type, officers process waste by burning it all this time, officers have never been given any training at all. making compost fertilizer in order to utilize organic waste and reduce the amount of waste. The aim of this community service activity is to form maintenance facility officers who care about the environment, and understand how to utilize organic waste into compost so that it can be used for plants on campus and is also economically valuable and can reduce the amount of organic waste generated. The method used is a contextual and participatory approach, with counseling, training and video screening models. This activity is carried out through several stages, namely the planning, training and evaluation stages. Evaluation activities were carried out by looking at the officers' knowledge before and after being given the training. The results showed that there was an increase in the average value and obtained a p-value of 0.04 < 0.05, meaning that there was a significant difference between the level of knowledge before and after being given the training. This service has been proven to increase the knowledge of Facility Care officers in processing organic waste into compost.